2-octyl cyanoacrylate sealing of the pancreatic remnant after distal pancreatectomy: a prospective pilot study - Hüttner, Felix; Probst, Pascal; Kenngott, Hannes Götz; Knebel, Phillip; Hackert, Thilo; Ulrich, Alexis; Büchler, Markus W.; Diener, Markus K. (PLOS ONE, 2018)
Background Postoperative pancreatic fistula (POPF) remains a frequent problem especially after distal pancreatectomy. The application of 2-octyl cyanoacrylate showed promising results in the reduction of POPF after pancreatoduodenectomy prompting an expansion of this technique to distal pancreatectomy. Thus, the objective of the current study was to assess safety, feasibility and preliminary efficacy of an intraoperative 2-octyl cyanoacrylate application after distal pancreatectomy. Methods Between April 2015 and June 2016 adult patients scheduled for elective distal pancreatectomy were considered eligible for the study. It was planned to include a total of 35 patients. After distal pancreatectomy with hand-sewn closure of the pancreatic remnant, a 2-octyl cyanoacrylate surgical glue was applied to the cut surface of the pancreas. Patients were followed up for three months with main focus on safety in terms of (serious) adverse events. Further endpoints included POPF, other pancreas-specific and surgical complications. Results 15 patients were included in the study because the manufacturer stopped production and distribution of the investigational device thereafter. There was a total of ten serious adverse events but no device-related events and no mortality. The serious adverse events depicted a typical safety profile after distal pancreatectomy. POPF occurred in five cases (33.3%), delayed gastric emptying and post-pancreatectomy haemorrhage in two cases respectively (13.3%). Conclusions Application of 2-octyl cyanoacrylate to the pancreatic remnant after distal pancreatectomy seems feasible and safe. The planned evaluation of preliminary efficacy was not possible due to the inadvertent early termination and subsequent small sample size of the study. Novel techniques for prevention and therapy of POPF should be evaluated in future trials.